Cover Feature: Breslow Intermediates (Amino Enols) and Their Keto Tautomers: First Gas‐Phase Characterization by IR Ion Spectroscopy (Chem. Eur. J. 8/2021). Issue 8 (7th December 2020) - Paul, Mathias; Peckelsen, Katrin; Thomulka, Thomas; Martens, Jonathan; Berden, Giel; Oomens, Jos; Neudörfl, Jörg‐M.; Breugst, Martin; Meijer, Anthony J. H. M.; Schäfer, Mathias; Berkessel, Albrecht
Abstract : Breslow Intermediates are of pivotal importance for chemical and biological Umpolung reactions catalyzed by N‐heterocyclic carbenes (NHCs). In the sense of John B. Fenn (NP 2002), attachment of a charge tag to these "molecular elephants" provides them with "electrospray wings", and for the first time allows their gase phase structural characterization by infrared multiple photon dissociation (IRMPD) spectroscopy. The enol‐ketone tautomerism of a number of NHC‐aldehyde combinations, crucial for their chemical reactivity, have been determined in the gas‐phase and interpreted by DFT calculations. More information can be found in the Full Paper by M. Breugst, A. J. H. M. Meijer, M. Schäfer, A. Berkessel, et al. on page 2662 .